Combined small‐incision lenticule extraction and intrastromal corneal collagen crosslinking to treat mild keratoconus: Long‐term follow‐up. Issue 11 (November 2015) - Graue‐Hernandez, Enrique O.; Pagano, Gabriela L.; Garcia‐De la Rosa, Guillermo; Ramirez‐Miranda, Arturo; Cabral‐Macias, Jesus; Lichtinger, Alejandro; Abdala‐Figuerola, Alexandra; Navas, Alejandro
Abstract : Purpose : To report visual, refractive, and topographic outcomes of sequential, same‐day small‐incision lenticule extraction and intrastromal corneal collagen crosslinking (CXL) in eyes with mild keratoconus. Setting : Institute of Ophthalmology Conde de Valenciana, Mexico City, Mexico. Design : Prospective interventional case series. Methods : Fifteen eyes with forme fruste keratoconus and/or irregular corneas, corrected distance visual acuity 20/40 or better, stable refraction of at least 1 year, age 18 years or older, and residual corneal thickness of greater tan 400 μm before performing collagen crosslinking were studied. Patients were treated with small‐incision lenticule extraction followed by intrastromal injection of riboflavin inside the pocket. Ultraviolet A light with a wavelength of 370 nm to 3 mW/cm 2 was applied for 30 minutes. Follow‐up was done at 1 day, at 1 week, and at 1, 3, 6, 12, 18, and 24 months. Results : Eight patients were included in the study. The mean age was 29.5 years ± 5.5 (SD) (range 20 to 36 years). Twenty‐four months of follow‐up were completed in 13 eyes, and 12 months were completed in 2 eyes. Preoperative uncorrected distance visual acuity improved from 1.6 ± 0.3 LogMAR (Snellen 20/796) to postoperative 0.12 ± 0.20 LogMAR (Snellen 20/26) and was statistically significant ( P < .001). Best‐corrected distance visual acuity did not change significantly ( P = .186), from 0.006 ± 0.02 LogMAR (Snellen 20/20) preoperatively to 0.04 ± 0.05 LogMAR (Snellen 20/21) postoperatively, and spherical equivalent improved from −4.3 ± 1.02 preoperatively to 0.2 ± 0.66 ( P < .001). Conclusion : Although further follow‐up and larger samples are needed to fully confirm these findings, the results suggest that combined small‐incision lenticule extraction and intrastromal corneal collagen crosslinking are a promising treatment option for patients for whom conventional laser refractive surgery is contraindicated. Financial Disclosure : Drs. Ramirez‐Miranda and Navas are consultants to Carl Zeiss Meditec. No other author has a financial or proprietary interest in any material or method mentioned.